Chronic energy deficiency (CED) and maternal diet is related to stunting incidence - Rosita Rosita; Lina Fitriani; Dyah Tahir; Yenni Yenni (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: One of the main causes of stunting is the lack of continuous energy intake in women of childbearing age (from adolescence, pre-conception to pregnancy) which results in Chronic Energy Deficiency during pregnancy which begins with the occurrence of "risk" and is characterized by low energy supply over a long period of time as measured by Upper Arm Circumference (LILA) of less than 23.5 cm or Body Mass Index (BMI) before pregnancy or The first trimester was below 18.5 Kg/m². Purpose: The purpose of this study is to determine the relationship between the history of SEZ in pregnancy and maternal diet with the incidence of stunting. Method: This study is analytical observational research with a cross-sectional research design which was carried out in the working area of the South Wara Health Center in June-July 2025. There are three variables in this study, namely the free variable, the SEZ in Pregnancy and the Maternal Diet the variable is tied to stunting. The collection of SEZ history data in mothers was obtained from mothers of toddlers through interviews, Maternal and Child Health (KIA) books and stunting data using secondary data sourced from the 2024-2025 EPPGBM big data of 62 children. Results: Based on the results of statistical data using the Chi-square test, the value  = 0.000 < (0.05) was obtained. Thus, it can be concluded that there is a relationship between diet and SEZ and stunting incidence. Conclusion: The results of the study show that there is a relationship between Chronic Energy Deficiency in pregnant women and diet with the incidence of stunting in the working area of the South Wara Health Center in 2025.The results of the study also show that there is a relationship between Diet and SEZ and the incidence of stunting in the working area of the South Wara Health Center, Palopo City in 2025. Suggestion: The results of this study are expected to increase public knowledge about the relationship between chronic energy deficiency in pregnancy and maternal diet and the incidence of stunting and can provide input to the public to better understand the importance of the health of pregnant women, especially during the 1000 days of their child's life, as well as prevent risks that may occur in the future by providing good nutrition to pregnant women and children     Keywords: KEK, Diet and Stunting